Investigating The Edmonton Symptom Assessment System (Esas) In Patients With Diabetic Foot Ulcers - Usman, Usman (International Journal of Health Sciences, 2025)
In addition to somatic ailments, individuals afflicted with DFU often manifest psychological maladies. Research on the psychological aspects of DFU patients has not yet been conducted, especially using the Edmonton Symptom Assessment System (ESAS) instrument. The aim is to predict the Edmonton Symptom Assessment System (ESAS) instrument among DFU Patients. This research conducted Descroptive Quantitative Research design. The sample in this study consisted of 57 DFU Patients who were selected by total sampling. The data collected in this study was analyzed descriptive Statistic. the majority of respondents are aged> 45 years as many as 53 respondents or 68.83%. Based on gender, it is found that the majority of respondents are female as many as 57 people or 74.03%. Based on the level of education, it was found that the majority of respondents graduated from elementary school totaling 31 people or 40.25%. Screening results on the Ankle Brachial Index found that the majority of respondents' ABI was Moderate, 31 people or 40.25%. While ESAS predictions are in the moderate category totaling 31 people or 40.25%.